Sains Modern, Sekularisme, dan Pendidikan Islam - Siti Hadiyanti Dini Islamiati; Muhammad Guntur Alting (Jurnal Dirosah Islamiyah, 2024)
The strong dominance of secularism in modern science is the biggest challenge in Islamic education. Islam is essentially not just a religion. Islam does not only deal with ritual matters. Islam also talks about science, justice, good deeds, and professionalism. In other words, Islam is not only about religion but also civilization. This research tries to explain the relationship between modern science and secularism as well as its impact on society, and also explains the solution in the context of Islamic education. The method used is a qualitative method, with data collection techniques in the form of documentation. The result of this research is the importance of integrating religious knowledge and science in the context of Islamic education, to create a unified concept, because all knowledge comes from Allah SWT. Socialization is not limited to higher education level, but also includes primary and secondary education, especially those under religious authority.